Intra-examiner and inter-examiner reliability in the determination of angular measurements of the wrist using a smartphone application - Wassmuth, Talita; Sakata, Mariana Saori Barboza; Paula, Andressa Morais de; Pereira, Wagner Menna; Ferreira, Luiz Alfredo Braun; Rossi, Luciano Pavan (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Purpose: With recent technological advances, goniometric applications have increasingly been used for the measurement of joint angles due to the greater practicality and accessibility. It is therefore important to determine the reliability of these applications. The evaluation of the wrist is important, as this joint is commonly affected by trauma that can lead to limitations of movement. Thus, the aim of the study was to determine the intra-examiner and inter-examiner reliability of the Goniometer PRO© smartphone application for measuring the range of motion of the wrist. Basic procedures: A correlational, blind, cross-sectional study was conducted involving 43 healthy women (mean age: 20 ± 2.3 years) with no upper limb injuries. Both wrists were examined in each participant (n=86). Active wrist flexion and extension were measured by three previously trained examiners using the smartphone application for the determination of inter-examiner reliability and a second evaluation was performed after 48 hours for the determination of intra-examiner reliability. Main findings: Excellent intra-examiner (ICC>0.75) and inter-examiner (ICC>0.90) reliability were found for both wrists. A very good correlation (r>0.90; p<0.0001) was found for the intra-examiner evaluation of the left wrist and good correlations (r>0.80; p<0.0001) were found for the right wrist and for the inter-examiner evaluations of both wrists. Good agreement was found for all measures, as demonstrated by the Bland-Altman analysis. Conclusions: The present data on intra-examiner and inter-examiner reliability of the Goniometer PRO© for the smartphone demonstrate that this goniometric application can be used as an effective tool for the evaluation of the range of motion of the wrist.